Denmark : a Lonely Planet travel survival kit - Bendure, Glenda; Friary, Ned, 1952- (Hawthorn, Vic., Australia ; Oakland, Calif., U.S. : Lonely Planet Publications, 1996)
This guide contains information needed for a visit to Denmark on any budget. It features a chapter on Copenhagen and also covers Legoland. Full coverage is given of campgrounds, hostels and hotels. Information on inter-island ferries, bus and train routes is also supplied.
Includes index.
Keywords: Denmark -- Guidebooks